2013
DOI: 10.1523/jneurosci.2451-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

TASK-2 Channels Contribute to pH Sensitivity of Retrotrapezoid Nucleus Chemoreceptor Neurons

Abstract: Phox2b-expressing glutamatergic neurons of the retrotrapezoid nucleus (RTN) display properties expected of central respiratory chemoreceptors; they are directly activated by CO 2 /Hϩ via an unidentified pH-sensitive background K ϩ channel and, in turn, facilitate brainstem networks that control breathing. Here, we used a knock-out mouse model to examine whether TASK-2 (K2P5), an alkaline-activated background K ϩ channel, contributes to RTN neuronal pH sensitivity. We made patch-clamp recordings in brainstem sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
142
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(167 citation statements)
references
References 36 publications
10
142
0
7
Order By: Relevance
“…One region that is involved in central respiratory chemoreception is the retrotrapezoid nucleus (RTN) (Guyenet et al 2010;Guyenet and Bayliss 2015;Nattie 2011). This region is located in the ventrolateral surface of the medulla with neurons that have a genetic lineage (derived from neurons that express PHOX2B, Atoh-1, and Egr-2) and express different phenotypes (PHOX2B, NK1 receptors, VGlut2, TASK-2, GPR4, and galanin but not GABA, glycine, acetylcholine, or catecholamines) (Kumar et al 2015;Lazarenko et al 2009;Ruffault et al 2015;Takakura et al 2008Takakura et al , 2014Wang et al 2013). In this concise review, we discuss, on the basis of clinical and genetic studies in human respiratory disease and evidence from neurophysiology and experimental animal models, how a restricted number of neurons, located in the VMS, expressing and depending on the PHOX2B transcription factor could be essential in the control of breathing and autonomic regulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One region that is involved in central respiratory chemoreception is the retrotrapezoid nucleus (RTN) (Guyenet et al 2010;Guyenet and Bayliss 2015;Nattie 2011). This region is located in the ventrolateral surface of the medulla with neurons that have a genetic lineage (derived from neurons that express PHOX2B, Atoh-1, and Egr-2) and express different phenotypes (PHOX2B, NK1 receptors, VGlut2, TASK-2, GPR4, and galanin but not GABA, glycine, acetylcholine, or catecholamines) (Kumar et al 2015;Lazarenko et al 2009;Ruffault et al 2015;Takakura et al 2008Takakura et al , 2014Wang et al 2013). In this concise review, we discuss, on the basis of clinical and genetic studies in human respiratory disease and evidence from neurophysiology and experimental animal models, how a restricted number of neurons, located in the VMS, expressing and depending on the PHOX2B transcription factor could be essential in the control of breathing and autonomic regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular pH changes mediate neuronal pH sensitivity in vitro (Kumar et al 2015;Mulkey et al 2004;Ritucci et al 2005;Wang et al 2013), presumably attributed to the simultaneous effects of pH on multiple ion channels (Kumar et al 2015;Putnam et al 2004). The correct identification of relevant central chemoreceptors is complicated by the fact that brain stem neurons very commonly respond to extracellular fluid acidification in vitro and that, equally common, some pH responses persist after blockade of action potential-dependent transmitter release with tetrodotoxin (Bayliss et al 2001;Kumar et al 2015;Mulkey et al 2004;Wang et al 2013). Such results have led others to theorize that all rCPG neurons could be equally sensitive to pH and to conclude that the entire respiratory network possesses central respiratory chemosensitivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TASK-2 is a K 2P channel that plays important physiologic roles (López-Cayuqueo et al, 2015), including cell volume regulation (Niemeyer et al, 2001;Barriere et al, 2003), renal bicarbonate reabsorption in the proximal tubules of the kidney (Warth et al, 2004), the central detection of CO 2 and O 2 by chemosensitive neurons implicated in breathing control (Gestreau et al, 2010;Wang et al, 2013), and in the hearing function through an essential role in cochlear outer sulcus cells possibly in K 1 recycling (Cazals et al, 2015). Certain patients with a predisposition to Balkan endemic nephropathy carry the T108P mutation in TASK-2 (Toncheva et al, 2014); TASK-2 mutant T108P does not generate any significant currents in heterologous expression experiments, and this lack of activity is consistent with a role in Balkan endemic nephropathy (Veale and Mathie, 2016).…”
Section: Task-2 and The K 2p Channel Gating Hypothesesmentioning
confidence: 99%
“…Bayliss's group found that knock down of the K+ channel and the G-protein coupled receptor attenuates the pH sensitivity in vitro and nearly abolishes the hypercapnic ventilatory reflex, the respiratory reflex that alters breathing to normalize PaCO 2, in vivo ( Figure 2) (Gestreau et al, 2010;Wang et al, 2013a;Kumar et al, 2015). Other ligand candidates that may activate chemosensitive areas include molecular CO 2 and bicarbonate in these finely pH tuned areas of the brain (Huckstepp & Dale, 2011;Guyenet, 2014a).…”
Section: Definitions Of Central Chemoreception and The Retrotrapezoidmentioning
confidence: 99%